Identification of Bird species in Wetlands around Siran Lake, Muara Kaman, Central Mahakam, East Kalimantan - Chandradewana Boer; Arie Prasetya; Rustam Rustam; Rita Diana (Tropical Small Island Agriculture Management, 2021)
The avifauna of tropical peat swamp forests in East Kalimantan has not been well documented because of the smallest peat area compared to central Kalimantan. The surveys were conducted using various methods in the Muara Siran peat swamp forests and surrounding areas of Lake Siran (heath forest and riparian) in East Kalimantan, Indonesia. These findings were recorded on a list of 80 bird species as well as in numerous noteworthy records. Wetlands are an essential habitat for many threatened and near-threatened bird species. We also discovered Gallinula tenebrosa in Siran Lake, a species that has not been seen in over a century. However, it has a wide distribution globally, including in Australia and the United States. In the peat swamp forest, we recorded Cymbirrhinchus macrurus and Ichtyophaga humilis, rare and widely distributed. We also found Dicrurus hottentotus and Dicrurus remifer, some species of Ferruginous Babbler, Trichastoma bicolor, and the White-necked Babbler, Stachyris leucotis. The Hook-billed bulbul Setornis criniger and the Sooty capped Babbler Malacopteron affinae are found in riparian forests. There are six species of woodpecker. Dryocopus javensis, Great Slaty Woodpecker, Mulleripicus pulverulentus, Meyglyptes tukki, Picus puniceus, and Sasia abnormis. Cuckoo-shrike Coracina striata and Pitta sordia were also discovered. Wetlands (peat swamp forest, heath forest, and riparian areas) should be better protected due to their importance to many species, particularly from destruction and loss of habitat caused by forest fires.